Heart rate variability of elite female rowers in preparation for and during the national selection regattas: a pilot study on the relation to on water performance - DeBlauw, Justin A.; Stein, Jesse A.; Blackman, Carolyn; Haas, Melissa; Makle, Seraya; Echevarria, Isis; Edmonds, Rohan; Ives, Stephen J. (Frontiers in Sports and Active Living, 2023)
Elite athletes require a delicate balance of physiological and psychological stress and recovery—essential for achieving optimal performance. Monitoring heart rate variability (HRV) provides a non-invasive estimation of both physiological and psychological stress levels, offering potentially valuable insights into health, performance, and adaptability. Previous studies, primarily conducted on male participants, have shown an association between HRV and performance in the context of rowing training. However, given the rigorous nature of rowing training, it is crucial to investigate HRV in elite rowers, particularly during the U.S. national selection regattas (NSR). Purpose To comprehensively analyze elite female rowers, evaluating acute changes in HRV and subjective psychometrics during the NSR. Methods Five elite female rowers (26 ± 2 years, 180 ± 8 cm, 82 ± 8 kg, 19 ± 6%fat) were recruited and tracked prior to and during NSR I and II. Morning HRV measures were completed using photoplethysmography (HRV4training) along with self-reported levels of fatigue, soreness, rating of perceived exertion, mentally energy and physical condition. Results Significant decreases were observed in log transformed root-mean square of successive differences (LnRMSSD; p = 0.0014) and fatigue (p = 0.01) from pre-to-during NSR, while mental energy (p = 0.01), physical condition (p = 0.01), and motivation (p = 0.006) significantly increased. These psychometric measures returned to pre-NSR levels, at post-NSR (all p < 0.05), though HRV remained slightly suppressed. NSR on-water performance was not correlated to LnRMSSD or the change in LnRMSSD (p > 0.05). Discussion HRV and psychometric measures are sensitive to the stress of elite rowing competition in females. However, HRV was not associated with on-water rowing performance during an elite rowing competition.